Influence of Grapheme and Syllable Learning on Handwriting Output of Chinese Characters in Children With Dictation Difficulties - Tan, Yaqian; Liu, Xiangping (Frontiers in Psychology, 2018)
Studies on Chinese dictation difficulties have focused on visual processing and phonological processing. Over recent decades, attention has shifted to the ability to bind visual and auditory information. However, such studies are scarce and have rarely focused on how this ability influences children’s learning and writing of Chinese characters. In this study, a group of children with Chinese dictation difficulties and a control group without such difficulties were instructed to learn rarely used Chinese characters under three learning modes: grapheme learning, syllable learning, and grapheme-syllable learning. Participants’ learning time and writing accuracy were recorded under each learning mode. Findings showed that under the grapheme learning mode, learning time and writing accuracy did not differ significantly between the two groups. However, under the grapheme-syllable learning mode, the writing accuracy of children with dictation difficulties was significantly lower than controls. These findings together suggested that for children with dictation difficulties, learning graphemes and syllables at the same time did not improve their writing performance as much as controls do. Under the syllable learning mode, learning time and writing accuracy did not differ significantly between the two groups. The findings contributed to a better understanding of Chinese dictation difficulties.